An Environment-Tolerant Ion-Conducting Double-Network Composite Hydrogel for High-Performance Flexible Electronic Devices - Zhao, Wenchao; Zhou, Haifeng; Li, Wenkang; Chen, Manlin; Zhou, Min; Zhao, Long (Nano-Micro Letters, 2024)
High-performance ion-conducting hydrogels (ICHs) are vital for developing flexible electronic devices. However, the robustness and ion-conducting behavior of ICHs deteriorate at extreme temperatures, hampering their use in soft electronics. To resolve these issues, a method involving freeze–thawing and ionizing radiation technology is reported herein for synthesizing a novel double-network (DN) ICH based on a poly(ionic liquid)/MXene/poly(vinyl alcohol) (PMP DN ICH) system. The well-designed ICH exhibits outstanding ionic conductivity (63.89 mS cm−1 at 25 °C), excellent temperature resistance (− 60–80 °C), prolonged stability (30 d at ambient temperature), high oxidation resistance, remarkable antibacterial activity, decent mechanical performance, and adhesion. Additionally, the ICH performs effectively in a flexible wireless strain sensor, thermal sensor, all-solid-state supercapacitor, and single-electrode triboelectric nanogenerator, thereby highlighting its viability in constructing soft electronic devices. The highly integrated gel structure endows these flexible electronic devices with stable, reliable signal output performance. In particular, the all-solid-state supercapacitor containing the PMP DN ICH electrolyte exhibits a high areal specific capacitance of 253.38 mF cm−2 (current density, 1 mA cm−2) and excellent environmental adaptability. This study paves the way for the design and fabrication of high-performance multifunctional/flexible ICHs for wearable sensing, energy-storage, and energy-harvesting applications. Highlights: 1 Novel double-network (DN) ion-conducting hydrogel (ICH) based on a poly(ionic liquid)/MXene/poly(vinyl alcohol) system (named PMP DN ICH) was synthesized using freeze–thawing and ionizing radiation technology. 2 The PMP DN ICH possesses a multiple cross-linking mechanism and exhibits outstanding ionic conductivity (63.89 mS cm−1), excellent temperature resistance (−60–80 °C) and decent mechanical performance. 3 The well-designed PMP DN ICH shows considerable potential in wearable sensing, energy storage, and energy harvesting.